Guiding The Perception and Behavior of Generation Z Regarding LGBT Issues in Digital Content Based on Age Characteristics - Ashabul Fadhli; Syelfia Dewimarni (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to determine the influence of parental supervision and its relationship with the perception and behavior of Generation Z regarding LGBT issues in digital content access. There is a common stigma that Generation Z, having grown up during a time of extensive internet use, is at greater risk of being exposed to LGBT culture. This field research employs a quantitative descriptive approach and Pearson Correlation (R). The research subjects are Generation Z individuals in Padang City, grouped by age characteristics: junior high school students aged 14-16 years, senior high school students aged 16-18 years, and university students aged 18-22 years. The sampling technique used is purposive sampling. The research instrument is a questionnaire arranged using a Likert scale. The results reveal that parental supervision has a significant influence with a score of 0.000 (p < 0.05) and a strong relationship with perception and behavior at 95.7%. This finding indicates the importance of parents providing relevant parenting patterns and education tailored to the needs of Generation Z. This research hopes to serve as a guide for parents and related institutions in safeguarding Generation Z’s online activities from LGBT influences and cultural exposure.